Piloting GETCare: A Goal-Based Education and Skills Training Program for Caregivers. Issue 6 (27th November 2022) - Einerson, Jackie; Cardell, Beth; Majersik, Jennifer J.; Reblin, Maija; Richards, Lorie Gage; Terrill, Alexandra L.
Abstract: Purpose: Many individuals with stroke require informal caregiver support. These caregivers are often unprepared and overwhelmed. This study assesses the feasibility and acceptability of GETCare, a remote Goal-based Education and skills Training program for Caregivers caring for an individual poststroke. Design: Single-arm mixed-methods pilot trial was performed. Methods: The GETCare program is a 5-week remote, individually administered program for informal stroke caregivers that includes education, skills training, guided goal setting, and resource recommendations. Quantitative data were analyzed using descriptive statistics and qualitative data via a deductive approach. Results: Twenty-eight caregivers were recruited with 18 caregivers completing the program. These 18 caregivers reported high satisfaction, and over 75% reported program content was at least quite helpful. Caregivers suggested that the length of the program was appropriate, indicated that weekly check-ins were helpful, and supported this program for informal caregivers across the time trajectory poststroke. Eight of 10 caregivers who dropped out of the program were caring for someone 0–4 months poststroke. Conclusions: Caregivers positively received the GETCare program, which was uniquely structured to provide resources and skills for this high-need population. This pilot study provides valuable insight for future remote interventions poststroke. Clinical Relevance to Practice of Nursing: Results provide foundational knowledge in how to better support caregivers through guided goal setting and individualized education.